Assessment of cardiovascular and renal functions during treatment with Desmodium adscendens therapy - Adinoyi, Seriki Samuel (Journal of Cardiology and Cardiovascular Medicine, 2020)
Desmodium adscendens is a rain forest medicinal herb used in managing quite a number of medical conditions. Its efficacy in the treatment of several diseases has made it a first line herb for doctors, especially in managing all forms of spasm. It is however common knowledge that some of these medicinal herbs impact severely on the normal functioning of some vital organs of the body during their administration. The present study was carried out to assess the renal and cardiovascular performance in subjects undergoing treatment with Desmodium adscendens with a view to advising against its indiscriminate use. The parameters used for the assessment of renal functions were serum creatinine and urea concentrations and their clearance. Also, changes in electrolyte concentration of Sodium, Potassium and Chloride concentration were used to assess cardiovascular performance. The histology of the kidney and heart tissues was also done to determine if the extract has impact on the cyto-architecture of the organs. Twenty-four (24) wistar rats were used for the experiment. The rats were grouped randomly into four groups (n = 6). Group 1 served as control, and the rats in the group were given normal rat feeds and water. Group 2 served as low dose group, and rats in this group were administered with low dose of extract 300 mg/kg. Group 3 served as medium group, and rats in this group were treated with medium dose of extract, 450 mg/kg. Group 4 served as high dose group, and rats in this group were treated with high dose of extract 600 mg/kg. The extract was administered for 28 days. Result showed that the extract did not impact negatively on the normal function of the renal and cardiovascular system of the treated groups, rather it enhanced their performances. It can therefore be concluded that the extract is beneficial to renal and cardiovascular functions if used within the treatment dosage.